Maternal Satisfaction towards Spinal Anesthesia for Cesarean Section - Thapa, Chitra; Gauchan, Sabin; Bimali, Sneha; Bhusal, Srijana (Journal of Institute of Medicine Nepal, 2022)
Introduction Patient satisfaction has become an important parameter to assess an overall quality of health care. We conducted this study to evaluate the level of maternal satisfaction with our anesthetic technique and to identify factors that compromise maternal satisfaction. Methods A descriptive cross-sectional study was conducted in two hundred patients who underwent cesarean section under spinal anesthesia after receiving ethical approval from the Institutional Review Committee (Ref. No.: 044-078/079). Preset questionnaires were asked in a face-to-face interview within 6 to 24 hours of cesarean section. Descriptive statistics was used to show frequency distribution and percentage of variables. Results The overall satisfaction level was 99%, with the lowest satisfaction level reported for pain therapy (88.5%). Subscale-wise, 90.5% of the patients were satisfied with the preoperative assessment and evaluation, 95% of the patients were satisfied with the intraoperative care and attention they received from their anesthetist, 97% of the patients were satisfied with their relationship with the anesthetist. More than 97% of the patients were satisfied with the level of care they received from their anesthetist. Conclusion In general, the overall maternal satisfaction towards spinal anesthesia was high (99%) in our population. To further increase our patient satisfaction we need to extend our services to the postoperative period as well.